Pengaruh penambahan tepung daun Indigofera (Indigofera zollingeriana) dalam pakan terhadap kandungan kimia telur Ayam Arab - Asis Surajat; Anita Mustika Ibrahim (Jurnal Ilmu Peternakan Terapan, 2021)
The aim of this research to study the effect of Indigofera zollingeriana leaf meal on the chemical quality of Arabian chicken eggs. The research was conducted for 3 months at the Permata poultry farm group, Wua - wua Village, Kendari. The analysis of protein, fat, and cholesterol content of Arabic chicken eggs was carried out at the Integrated Laboratory of the Institut Pertanian Bogor. The study used a completely randomized design (CRD) with 4 treatments and 4 replications. Experimental rations using the percentage of Indigofera zollingeriana leaf flour, such as: P0= 0%, P1= 10%, P2= 15%, and P3= 20% Indigofera leaf flour zollingeriana. The parameters observed were levels of protein, fat, and cholesterol level in Arabic chicken eggs. The research data used a completely randomized design (CRD), if the analysis had a real effect, carried out with the Duncan Multiple Range Test (DMRT). The results showed that the addition of Indigofera zollingeriana leaf on rations up to 20% did not have a significant effect on protein, fat, and cholesterol level of Arabic chicken eggs (P> 0.05). Using Indigofera zollingeriana leaf meal up to 20% in rations does not affect the chemical quality of Arabian chicken eggs.